Reflection of Maqāṣid al-Sharī'ah in the classical Fiqh al-Awqāf. Issue 2 (19th February 2020) - Abdullah, Mohammad
Abstract : Purpose: This paper aims to analyse the Sharī'ah premises of classical waqf doctrines followed by critically analysing the framework of waqf jurisprudence ( fiqh al-awqāf ) from a Maqāṣid al-Sharī'ah (the higher objectives of Islamic law) perspective. The objective of examining the jurisprudential framework of waqf from a maqāṣid perspective is to contextualise the scope of dynamism and innovation in the modern waqf structure. Design/methodology/approach: For examining the jurisprudential aspects of classical fiqh al-awqāf with a special reference to Maqāṣid al-Sharī'ah, the paper analyses the classical waqf books and treatises from the four Sunni schools of jurisprudence by employing a textual analysis method. Findings: The paper finds that the key constituents of maqāṣid are interwoven in the classical discourse of waqf rulings. It finds that in deriving the principles of waqf, the jurists ensured that the essentialities of Maqāṣid al-Sharī'ah are subtly intermingled with the necessary components of fiqhī principles. Deconstructing the applied analogical reasoning of the classical jurists in deriving the waqf rulings, this paper provides recommendations for maqāṣid -oriented application of waqf in the modern context. Research limitations/implications: This study does not cover either the historical contribution of waqf among the Muslim societies nor does it touch on the empirical aspects of modern waqf . Rather, the focus of the study is limited to analysing the classical jurisprudential rulings of waqf and their distillation process from a Maqāṣid al-Sharī'ah perspective. The study has good implication for modern awqāf, which need to be created, managed and directed in the spirit of Maqāṣid al-Sharī'ah. Practical implications: The key objective of adopting the maqāṣid framework for the analysis of fiqh al-awqāf in its classical permutations is to learn how to utilise the maqāṣid approach as a baseline for the deduction of new waqf rulings in a contextualised term. Originality/value: The novelty of the paper lies in its examination of the classical waqf rulings distillation process, and the cogent intersection of Maqāṣid al-Sharī'ah with the principles of fiqh . By delving into the Sharī'ah premises of classical waqf jurisprudence through the lens of maqāṣid, the paper adds an original value and fills an existing gap in the available literature.